Oral Health-Related Quality of Life in Young Adults: A Survey of Russian Undergraduate Students - Drachev, Sergei; Brenn, Tormod; Trovik, Tordis A (International Journal of Environmental Research and Public Health, 2018)
Published in International Journal of Environmental Research and Public Health . Source at https://doi.org/10.3390/ijerph15040719 . Background : Oral health (OH) is poor among young adults in Russia, but there is little information on OH-related quality of life (OHRQoL) in this population. We investigated how socio-demographic factors, self-reported OH characteristics, oral health behaviour, and clinically-assessed OH are related to OHRQoL in medical and dental students in North-West Russia. Methods : This cross-sectional study included 391 medical and 275 dental Russian undergraduate students aged 18–25 years. Information on socio-demographic, self-reported OH characteristics, and oral health behaviour was obtained from a structured, self-administered questionnaire. A clinical examination was performed to assess dental caries experience based on the decayed (D) missing (M) filled (F) teeth (T) index; Simplified Oral Hygiene Index; and Gingival Index. OHRQoL was measured by the OH Impact Profile (OHIP-14). Results : 53.6% of students reported low OHRQoL during the last 12 months. Female sex (odds ratio [OR] = 1.48, 95% confidence interval [CI]: 1.00–2.19), rural place of childhood residence (OR = 1.56, 95% CI: 1.06–2.28), poor self-assessed dental aesthetic (OR = 1.75, 95% CI: 1.16–2.64), dissatisfaction with mouth and teeth (OR = 2.51, 95% CI: 1.68–3.77), and DMFT index (OR = 1.05, 95% CI: 1.01–1.09), were all significantly, independently associated with low OHRQoL. Conclusion : Socio-demographic factors (rural place of childhood residence, female sex), poor self-reported OH characteristics, and high DMFT index were associated with low OHRQoL.